(untitled) (Comprehensive Journal of Science, 2025)
The present study focused on the effect of the main milling parameters such as rating feed ,speed and depth of cutting , and other factors were constant such as cooling condition were air cooling and milling tool type were four cutting edge tool with carbide coated insert and the study was carried out by machining C60 .Also in the presents study of the Taguchi method were applied to optimize surface quality in a CNC milling machine .An orthogonal array of L9 and MINTTAB16 were applied .The surface roughness values were obtained from the regression model are very close to the true values.